Theoretical analysis of Li-8+Pb-208 reaction and the critical angular momentum for complete fusion - Mukeru, B. [UNESP]; Lekala, M. L.; Lubian, J.; Tomio, Lauro [UNESP] (Elsevier B.V., 2020)
In a theoretical approach, the complete and incomplete fusions are investigated by considering the Li-8 + Pb-208 reaction, within a three-body model where the projectile is described as n-Li-7 with binding energy epsilon(b). By decreasing epsilon(b) from its known experimental value, the complete fusion is shown to have no meaningful dependence on such variations, whereas the incomplete fusion strongly depends on that. The complete and incomplete fusion cross sections are calculated by using a combination of both continuum-discretized coupled-channel and sum-rule models. To this end, an incident-energy dependent cut-off angular momentum L-c is first obtained by using the available complete fusion experimental data, within an approach which is extended to model results obtained for other incident-energies. An approximated fitted expression linking L-c to the well-known critical value L-crit derived by Wilczynski (1973) [28] suggests that the sum-rule model could be generalized to energies around and below the Coulomb barrier. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Nuclear fusion reactions; Cross sections; One-neutron halo nuclei; Lithium-8; Pb-208; Critical angular momentum